2019
DOI: 10.1177/0957650919844045
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on pre-film atomization mechanism and characteristics by a coaxial swirl injector

Abstract: The overall process and mechanism of the centrifugal pre-film atomization with double swirling flow were studied using the methods of large Eddy simulation and volume of fluid. The atomization process includes a centrifugal jet under the primary swirl and a pre-film atomization under the two-stage counter-rotating swirl at the venturi outlet. The fuel is ejected from the outlet of the centrifugal nozzle and undergoes the transient process of reaching the venturi throat. The breaking mechanism of liquid film in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In the study of the vortex, it is believed that there is a backflow area inside the swirl nozzle and the K-H surface wave is captured. Zhang et al [5] used LES and VOF to study the entire process of dual-cyclone centrifugal pre-film atomization. The study found that collisions and waves promote the expansion of the liquid film, which is consistent with the flow characteristics given in the experiment.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of the vortex, it is believed that there is a backflow area inside the swirl nozzle and the K-H surface wave is captured. Zhang et al [5] used LES and VOF to study the entire process of dual-cyclone centrifugal pre-film atomization. The study found that collisions and waves promote the expansion of the liquid film, which is consistent with the flow characteristics given in the experiment.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that increasing the ambient pressure increased the size of droplets in all of the spray regions, with decreased secondary atomization. Zhang et al researched the overall process of double swirl atomization using the methods of large eddy simulation and volume of fluid [13]. In the simulation, they observed two wave patterns in the development of spray, with variable droplet size distribution.…”
Section: Introductionmentioning
confidence: 99%